The IISS armed conflict survey 2019 the worldwide review of political and humanitarian trends in current conflicts - Voronkova, Anastasia (Routledge for the International Institute for Strategic Studies, 2019)
The Armed Conflict Survey provides in-depth analysis of the political, military and humanitarian dimensions of all major armed conflicts, as well as data on fatalities, refugees and internally displaced persons. Compiled by the IISS, publisher of The Military Balance, it is the standard reference work on contemporary conflict. The book assesses key developments in 36 high-, medium- and low-intensity conflicts, including those in Iraq, Syria, Afghanistan, South Sudan, Israel-Palestine, Southern Thailand, Colombia and Ukraine